Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                

Bernoulli's Equation1

Download as pdf or txt
Download as pdf or txt
You are on page 1of 7

Differential Equations

MAT 052

Prepared by: EMT

MAT 052 1

Bernoulli’s Equation

MAT 052 2

1
Learning Objectives:

At the end of the lesson, students should be


able to:
A. Transform a given DE to a possible standard
form of Bernoulli differential equation
B. Find the integrating factor for a first ordered
linear differential equation
C. Solve a Bernoulli differential equation by the
use of given or found integrating factor

MAT 052 3

Bernoulli’s Equation

Definition: Bernoulli’s Equation are nonlinear


DE that can be transformed into linear ODE.
They have the form:
dy
+𝑃 𝑥 𝑦 =𝑄 𝑥 𝑦
dx
 where 𝑛 is a real number, 𝑛 ≠ 1 or 0.

MAT 052 4

2
Steps:
𝑀 𝑥, 𝑦 𝑑𝑥 + 𝑁 𝑥, 𝑦 𝑑𝑦 = 0
1. Put the DE into this form: Bernoulli’s
Equation
+𝑃 𝑥 𝑦 =𝑄 𝑥 𝑦
2. Get the integrating factor 𝐼𝐹:
 
( ) ∫  ( )
𝐼𝐹 = 𝑒
3. Use the formula:  

𝑦( )
𝐼𝐹 = 1 − 𝑛 𝑄 𝑥 𝐼𝐹 𝑑𝑥 + 𝐶
 
MAT 052 5

Bernoulli’s Equations:

dy
+𝑃 𝑥 𝑦 =𝑄 𝑥 𝑦
dx

 Solution:  
   
( ) ( ) ∫  ( ) ∫  ( )
𝑦 𝑒 = 1−𝑛 𝑄(𝑥)𝑒 𝑑𝑥 + 𝐶
 

MAT 052 6

3
Solve the DE .
1. Put the DE into this form: Bernoulli’s Equation
+𝑃 𝑥 𝑦 =𝑄 𝑥 𝑦

𝑦 = 𝑦 − 𝑥𝑦 𝑒
𝑦 − 𝑦 = −𝑥𝑒 𝑦

𝑃 𝑥 = −1 𝑄 𝑥 = −𝑥𝑒 𝑛=3

MAT 052 7

2. Get the integrating factor 𝐼𝐹: 𝑃 𝑥 = −1


 
𝐼𝐹 = 𝑒 ( ) ∫  ( ) 𝑛=3
 
𝐼𝐹 = 𝑒 (   ) ∫ 
= 𝑒   ∫ 
= 𝑒 ∫ 
=𝑒

MAT 052 8

4
 
3. Use the formula: 𝑦 ( )
𝐼𝐹 = 1 − 𝑛 ∫  𝑄 𝑥 𝐼𝐹 𝑑𝑥 + 𝐶
 

𝑦( )
𝐼𝐹 = 1 − 𝑛 𝑄 𝑥 𝐼𝐹 𝑑𝑥 + 𝐶
   
𝐼𝐹 = 𝑒
( )
𝑦 𝑒 = 1−3 𝑥𝑒 𝑒 𝑑𝑥 + 𝐶
  𝑄 𝑥 = −𝑥𝑒
 
𝑦 𝑒 = −2   −𝑥𝑒 𝑒 𝑑𝑥 + 𝐶 𝑛=3
 
𝑦 𝑒 =2 𝑥𝑑𝑥 + 𝐶
𝑥  
𝑦 𝑒 =2 +𝐶
2
𝑦 𝑒 =𝑥 +𝐶
𝑦 𝑒 =𝑥 +𝐶 𝑦
𝑒 =𝑦 𝑥 +𝐶

MAT 052 9

Solve the DE
1. Put the DE into this form: Bernoulli’s Equation
+𝑃 𝑥 𝑦 =𝑄 𝑥 𝑦

𝑥 + 6𝑦 𝑑𝑥 − 4𝑥𝑦𝑑𝑦 = 0
1
𝑥 + 6𝑦 𝑑𝑥 − 4𝑥𝑦𝑑𝑦 = 0
−4𝑥𝑦 𝑑𝑥
𝑥 6𝑦 𝑑𝑦
+ + =0
−4𝑥𝑦 −4𝑥𝑦 𝑑𝑥 3
𝑃 𝑥 =−
𝑑𝑦 3 𝑥 2𝑥
− 𝑦− =0 𝑥
𝑑𝑥 2𝑥 4𝑦
𝑄 𝑥 =
𝑑𝑦 3 𝑥 𝑑𝑦 3 𝑥 4
− 𝑦= ⟹ − 𝑦= 𝑦 𝑛 = −1
𝑑𝑥 2𝑥 4𝑦 𝑑𝑥 2𝑥 4
MAT 052 10

5
2. Get the integrating factor 𝐼𝐹: 3
  𝑃 𝑥 =−
𝐼𝐹 = 𝑒 ( ) ∫  ( ) 2𝑥
 
𝑛 = −1
( ) ∫ 
𝐼𝐹 = 𝑒  
∫ 
=𝑒  
∫ 
=𝑒
=𝑒
=𝑒
=𝑥

MAT 052 11

 
3. Use the formula: 𝑦 ( )
𝐼𝐹 = 1 − 𝑛 ∫  𝑄 𝑥 𝐼𝐹 𝑑𝑥 + 𝐶
 

𝑦( )
𝐼𝐹 = 1 − 𝑛 𝑄 𝑥 𝐼𝐹 𝑑𝑥 + 𝐶
   
𝑥 𝐼𝐹 = 𝑥
𝑦( )
𝑥 = 1 − −1 𝑥 𝑑𝑥 + 𝐶
  4 𝑥
𝑥   𝑄 𝑥 =
𝑦 𝑥 =2   𝑑𝑥 + 𝐶 4
4 𝑛 = −1

𝑦 𝑥 = 𝑥 𝑑𝑥 + 𝐶
4
1  𝑥
𝑦 𝑥 = +𝐶
2 −1
1
𝑦 𝑥 =− 𝑥 +𝐶
2
1
𝑦 𝑥 =− 𝑥 +𝐶 2𝑥 ⟹ 2𝑦 = −𝑥 + 𝐶𝑥
2
MAT 052 12

6
2𝑦 = −𝑥 + 𝐶𝑥 𝑥 = 1, 𝑦 = 1
2 1 =− 1 +𝐶 1
2 = −1 + 𝐶
𝐶=3
2𝑦 = −𝑥 + 𝐶𝑥

2𝑦 = −𝑥 + 3𝑥
2𝑦 = 𝑥 3𝑥 − 1

MAT 052 13

SQ 1 whole (by pair)

Solve the following DE:


a. 𝑦 − 2𝑥𝑦 𝑑𝑥 + 3𝑥 𝑑𝑦 = 0
b. 𝑥 𝑦𝑑𝑥 + 3𝑥 − 𝑦 𝑑𝑦 = 0

MAT 052 14

You might also like